Analisis pengelolaan kebun hutan (forest garden) oleh masyarakat Dayak Deah di Desa Pangelak Kabupaten Tabalong - Kharmaini Mubarak; Hafizianor Hafizianor; Ahmad Yamani (Jurnal Sylva Scienteae, 2024)
ABSTRACT. The Forest Garden for the Dayak Deah community is a symbol of their survival where the results can provide additional income. The management of the gardens uses an intercropping system, which means a mixed cropping form involving two or more types of plants in one area of planting land at the same time or somewhat simultaneously, some forest villagers use a monoculture or mixed system. This research aims to analyze the management and vegetation of the Dayak Deah community forest garden in Pangelak Village. Data analysis used is the descriptive analysis of its management and data analysis of vegetation found in community forest gardens. The results obtained are that the majority of the Dayak Deah people work as rubber farmers in supporting their daily lives, rubber is sold to collectors once a week where some of it can be stored, and the produce from forest garden fruits as additional income for the Dayak Deah people with forest garden management modern and traditional, modern in nature, namely using chemical drugs in the management of forest gardens and traditionally by logging, planting, slashing, as well as the IVI at the tree level, it can be seen that for the tree level on community land, the highest IVI was for the Durian type of 115%, followed by Cempedak with a value of 35% and Langsat of 32%, for the lowest IVI at the tree level is Jengkol which is 19%, Rubber with a value of 20% and Papaken with a value of 23% where based on the results of analysis of plant vegetation IKSMP is obtained by 0.8743 (high) and evenness index Simpson of 0.5304 (moderately or somewhat evenly)..